Consumer Responses to the Food Industry’s Proactive and Passive Environmental CSR, Factoring in Price as CSR Tradeoff - Kim, Yeonsoo (Journal of business ethics, 2017)
This study examines consumer reactions to the food industry’s environmental corporate social responsibility (CSR) by varying levels of CSR and price as CSR tradeoffs. Findings reveal that proactive CSR programs generate more favorable attitudes toward and stronger intent to purchase from the company compared to passive CSR programs. Supportive communication intention also increases with CSR level in the low price condition. Regarding the impact of price, respondents showed more positive attitudes toward a company that charges cheaper prices in general. However, when a company demonstrates proactive initiatives, respondents did not distinguish between prices and showed generally positive intent to support and intent to purchase from the company. When a company practices passive CSR and offers cheaper products, respondents showed the weakest supportive and purchase intentions.